Synthesis of Fe3O4 Nanocatalyst Capped Citric Acid (Fe3O4-CA) from Sargassum filipendula - Pratiwi, Dian (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2021)
The nanocatalyst Fe3O4 capped citric acid (Fe3O4-CA) was successfully synthesized using brown seaweed Sargassum filipendula. Sulfated polysaccharides contained in Sargassum filipendula extract contain sulfate, hydroxy, and aldehyde groups which cause Fe3+ reduction and nanoparticle stabilization. The FT-IR results of Sargassum filipendula extract showed the presence of CO-SO3 stretching vibrations at 1040 cm-1, sulfate groups at 1241 cm-1, aromatic CC at 1413 cm-1, carbonyl at 1604 cm-1, CH stretching vibrations at 2932 cm-1. 1, and the hydroxy group at 3316 cm-1Ṁeanwhile, citric acid was used as capping to prevent agglomeration of the synthesized nanocatalyst. Fe3O4-CA nanocatalysts were characterized using XRD, PSA, and SEM-EDX. The XRD results were processed using the Debye-Scherrer equation and the crystal size of Fe3O4-CA was 8.5 nm. PSA results show that Fe3O4-CA particles have a radius of 45.09 nm or diameter of 90.18 nm. This nanocatalyst was also tested for the synthesis of pyrimidine-derived compounds at optimum conditions using 7.5% mol of catalyst, 50 °C for 6 hours, in order to obtain a yield of 83.2%.